The Influence of Transformational Leadership, Organizational Commitment and Work Motivation as Intervening Variables on Job Satisfaction of ASN Employees of the East Jakarta City Education Department - Rohmad Budiyono; Kasmir Kasmir (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to analyze the elements affecting ASN employees' job satisfaction in the East Jakarta City Administration Education Department. The benefit the goal of this study is to address the issue of job satisfaction. for ASN employees of the East Jakarta City Administration Education Sub-dept. The East Jakarta City Administration's ASN employees make up the study's population. Education Sub-dept. using 104 employees as the sample size and an observation period of 2023. This research is quantitative research with data analysis methods using Structural Equation Model-Partial Least Square (SEM-PLS). The results of the research show that transformational leadership and organizational commitment have a positive and significant effect on work motivation, transformational leadership and organizational commitment have a positive and significant effect on job satisfaction, transformational leadership and organizational commitment have a positive and significant effect on job satisfaction through work motivation.